Acuerdos de aprovechamiento de actividad menor para la conservación de la fauna silvestre en comunidades de la Reserva Nacional Matsés, Loreto. 2024 - Diaz Romayna, Rosangelica (2024)
The purpose of the study is to evaluate the effectiveness of wildlife conservation strategies implemented in indigenous and peasant communities in the Matsés National Reserve. It is a non-experimental quantitative research of the exploratory type - descriptive, analytical, horizontal, on the Minor Activity agreements between SERNANP and head of the Matses community of the new San Juan Annex 37 beneficiaries, Río Gálvez and the head of the Concordancia native community, seven beneficiaries of the Tapiche River, to take advantage of the wild fauna resource, the control and monitoring instruments identified in the agreements for control and monitoring were used, mainly the Use Registry, which allowed the conclusion of the use of the wild fauna resource within the Reserve. National Matses (RNT) are made viable through Minor Activity Agreements. Which grants exploitation rights to Nuevo San Juan of the native community Matses and Concordancia, a peasant community over six (06) and four (04) respectively of wildlife species Pecari tajacu, Tayassu pecari, Cuniculus paca, Mazama Americana Mazama nemorivaga and Dasyprocta punctata, in areas of direct use: Loboyacu-Gálvez and Quebrada Alemán, with a use quota for the Nuevo San Juan community of 30 kg per month/beneficiary family and 200 kg per year/beneficiary family and an ancestral quota of 40 kg 40 / benefited family; While in Concordancia the quota is 20 kg monthly/beneficiary family and 150 kg annually/beneficiary family and an ancestral quota of 40 kg/beneficiary family, this right granted for Nuevo San Juan covers an area of 365,836.89 ha. until March 2026, and for the annex it matches with an area of 26,287.21 ha. until June 2026. The amount of bush meat extracted in Nuevo San Juan and Concordancia is well below the amount considered in the agreement in both communities and in the years evaluated, so unrestricted compliance with the Agreement is verified. of Minor Activity of wildlife exploitation in the RNM and the alternative hypothesis is accepted that states that agreements for the exploitation of minor activity have a positive impact on the conservation of the prioritized fauna resource in the Matsés National Reserve. Keywords: Matsés native community, Minor activity, Agreements